Unveiling The Hidden Mathematics In Traditional Indonesian Culinary Art: An Exploration of Knot Theory And Alexander Polynomial in Ketupat Telur - Ja'faruddin, Ja'faruddin (Universitas Cokroaminoto Palopo, 2024)
This research delves into the intriguing relationship between mathematical concepts and traditional Indonesian cultural heritage, particularly in the context of ketupat telur. By applying the theory of knots (knot theory) as a field of topology, the study aims to identify geometric patterns that underlie the making of ketupat telur, as well as to understand the role of symmetry in the formation of knots. The main focus of this research is the ketupat telur knot diagram with 13 points of intersection and Alexander polynomial calculations, as an alternative method for obtaining knot polynomials. The results of the geometric structure analysis of ketupat telur with Alexander polynomial calculations yield: Ak=-t3+7t2-18t+23-18t-1+7t-2-t-3 This finding produces a polynomial that reflects its geometric and structural properties. This illustrates how fundamental mathematical concepts such as knots and polynomials can be applied to culture to achieve a deeper understanding of both.